2018
DOI: 10.1186/s12894-018-0409-5
|View full text |Cite
|
Sign up to set email alerts
|

Multiparametric ultrasound: evaluation of greyscale, shear wave elastography and contrast-enhanced ultrasound for prostate cancer detection and localization in correlation to radical prostatectomy specimens

Abstract: BackgroundThe diagnostic pathway for prostate cancer (PCa) is advancing towards an imaging-driven approach. Multiparametric magnetic resonance imaging, although increasingly used, has not shown sufficient accuracy to replace biopsy for now. The introduction of new ultrasound (US) modalities, such as quantitative contrast-enhanced US (CEUS) and shear wave elastography (SWE), shows promise but is not evidenced by sufficient high quality studies, especially for the combination of different US modalities. The prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 48 publications
1
21
0
2
Order By: Relevance
“…Meanwhile, to investigate the feasibility of multiparametric US, machine learning by means of a Gaussian mixture model using only CEUS features already achieved a higher detection performance than individual parameters, increasing the accuracy from 73 % to 81 % [10]. Thus, in collaboration with clinical partners at the Academic Medical Centre (University of Amsterdam, Amsterdam, The Netherlands) and the Martini Klinik in Hamburg (University Hospital, Hamburg-Eppendorf, Germany), I conducted the first clinical study combining B-mode US, CEUS, its quantification, as well as shear-wave elastography [11]. A total of 50 patients referred for radical prostatectomy were enrolled in this study; my preliminary work on registration allowed me to accurately match the histopathology to the imaging planes and automatically segment the prostate.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, to investigate the feasibility of multiparametric US, machine learning by means of a Gaussian mixture model using only CEUS features already achieved a higher detection performance than individual parameters, increasing the accuracy from 73 % to 81 % [10]. Thus, in collaboration with clinical partners at the Academic Medical Centre (University of Amsterdam, Amsterdam, The Netherlands) and the Martini Klinik in Hamburg (University Hospital, Hamburg-Eppendorf, Germany), I conducted the first clinical study combining B-mode US, CEUS, its quantification, as well as shear-wave elastography [11]. A total of 50 patients referred for radical prostatectomy were enrolled in this study; my preliminary work on registration allowed me to accurately match the histopathology to the imaging planes and automatically segment the prostate.…”
Section: Resultsmentioning
confidence: 99%
“…This provides important advantages with data sets exhibiting clear spatial dependencies. In addition to the analysis of DCE-US data, combination with other (ultrasound) modalities reflecting different physical phenomena, such as B-mode acquisitions and shear wave elastography, represent a promising approach to boost the diagnostic accuracy (Brock et al 2013;Postema et al 2015;Mannaerts et al 2018Mannaerts et al , 2019Li et al 2019).…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…In addition to promoting the standardization of UCA injection and acquisition protocols, and of qualitative interpretation of DCE-US exams, important steps have been made in quantitative analysis, with the publication of consensus papers providing guidelines for quantification of tumor perfusion by DCE-US (Dietrich et al 2012;Leen et al 2012). Moreover, important steps to combine quantitative parameters extracted from DCE-US and other ultrasound modalities in a multiparametric fashion are also being made (Acharya et al 2011;Brock et al 2013;Postema et al 2015;Mannaerts et al 2018Mannaerts et al , 2019Theek et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Early diagnosis and effective treatment are the basis for ensuring a good prognosis in patients with prostate cancer [1,2]. Previous studies have shown that ultrasound molecular imaging provides new ideas for early diagnosis, treatment and efficient monitoring of prostate cancer because of its realtime dynamic imaging, therapeutic controllability and easy operation [3,4]. However, due to the poor sensitivity and specificity of conventional ultrasound diagnosis of prostate cancer, the development of a high-sensitivity contrast-enhanced ultrasound contrast agent is pertinent in ultrasound molecular imaging of prostate cancer [5].…”
Section: Introductionmentioning
confidence: 99%